Earnings management in Japan. - Seah, Wan Lin. (2009)
We investigate how the companies under keiretsu manage their earnings compared to the non-keiretsu in the Japanese market during two periods, namely 1988-1997 and 1998-2007. Using the modified Jones model, which measures the management of reported earnings through discretionary accruals, this paper finds that the progression in time has continued to reveal significantly greater earnings management among non-keiretsu than keiretsu firms. This can be attributed to greater monitoring ability among the keiretsu firms. Interestingly, we find that the magnitude of difference in discretionary accruals between keiretsu and non-keiretsu firms is smaller for the 1998-2007 period than 1988-1997 period. This phenomenon may be a result of dilution of cross shareholdings among the keiretsu firms. Despite this, the sustained significant level of cross shareholdings among the keiretsu firms still manage to keep a lower earnings management level than the non-keiretsu firms. With this report, we illustrate keiretsu firms’ progress towards an earnings reporting environment with greater manipulation over time.